Foresight Methods in Pedagogical Design of University Learning Environment. Issue 8 (2017) - Ju, Rong; Buldakova, Natalya V.; Sorokoumova, Svetlana N.; Sergeeva, Marina G.; Galushkin, Alexander A.; Soloviev, Andrey A.; Kryukova, Nina I.
No abstract available